Perkembangan pendidikan di era globalisasi - Iftina Delfi; Hudaidah Hudaidah (Peneliti.net, 2021)
The development in the era of globalization is so fast that the demands for human resources are increasing to face the progress of the times. This aspect of demands is due to problems that are difficult to predict quickly in terms of information technology and culture. This article aims to explain 1). The task of educational institutions or institutions is to create graduates who can compete and contribute globally, 2). Educational problems and educational strategies, 3). The role of teachers in the development of education. The method used in this article uses a literature approach by looking for relevant sources related to this theory. The results of several studies explain that the era of globalization has changed the way of thinking about education. The changes made were not just the way of teaching, but changes in the perspective of the concept of education itself. Development of current and future curricula must complement students' abilities in the pedagogic and life skills dimensions. In conclusion, the development of education in this era of globalization is very fast, so a professional teacher in the midst of advances in information technology in the learning process is still needed.